If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 8) = (4X + -28) Reorder the terms: (8 + X) = (4X + -28) Remove parenthesis around (8 + X) 8 + X = (4X + -28) Reorder the terms: 8 + X = (-28 + 4X) Remove parenthesis around (-28 + 4X) 8 + X = -28 + 4X Solving 8 + X = -28 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 8 + X + -4X = -28 + 4X + -4X Combine like terms: X + -4X = -3X 8 + -3X = -28 + 4X + -4X Combine like terms: 4X + -4X = 0 8 + -3X = -28 + 0 8 + -3X = -28 Add '-8' to each side of the equation. 8 + -8 + -3X = -28 + -8 Combine like terms: 8 + -8 = 0 0 + -3X = -28 + -8 -3X = -28 + -8 Combine like terms: -28 + -8 = -36 -3X = -36 Divide each side by '-3'. X = 12 Simplifying X = 12
| 2.5(2+z)=5(z+2.5) | | y=1.5-1 | | A=6F+4g | | 5x-2(7x-1)=14x | | 4Y^2+x^2=4 | | 3a-2=5 | | 4Y^2+x^2= | | 7(X-5)=71 | | 35x+7=11x+4 | | 4z=6z+2 | | Logx=2.4 | | 2x-4y+z=0 | | 8(2z-5)=4n+8 | | 3-8+2x=11+6x | | p/20=8/4 | | [-2+6x]+3=59 | | 5.79x-3.14y=-13.54 | | 3(2-0.9q)+(-1.3h-4)= | | -3(4t-4)+6t=5t-9 | | x^2+8+14=0 | | 4x-10+2x=8 | | f+g=f+h | | x^2+814=0 | | x^2+8+14= | | 6-(-5r)=5r+6 | | -8x+32-5=-5-9x | | sec(x)sin(x)-2sin(x)=0 | | 4x-32+20=5 | | 3*x+2-8=3*x | | sex(x)sin(x)-2sin(x)=0 | | 12.50+0.15t=20 | | X^2+10x+52=0 |